UML Modeling for Dynamic Logistics System Based on DEVS - Zhang Zhiyong; Liu Jie; Zhang Xinhui (Institute of Advanced Engineering and Science, 2013)
DEVS is a hierarchical and modular system descriptive method. However, it cannot describe dynamic process and relationship of system members. This article has proposed a way to extend UML using stereotype, making it suitable for simulation modeling. To build a modeling tool, we defined atomic model class and coupled model class, both of which are in line with not only DEVS’s hierarchical and modular requirements but also UML’s object-oriented characteristics. At last, we use the tool to analyze and build UML models for a dynamic logistics system, the container berth system, making it easier to implement on simulation platform. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2397